Social Support Description For a Mother With Depression and Anxiety Disorders After the Death of Her Child - Babyazka Sandrina Triwidya; Alifia Ulie Mizana Hadori (Green Publisher Indonesia, 2025)
Grieving is a process that cannot be determined in terms of duration, form, or reaction. Losing someone close, especially a child, can significantly impact the parents. Social support can play an important role in helping parents cope with the grieving process and adjust to life after loss. This study aims to describe the social support of a mother with depression and anxiety disorders after the death of her child. A qualitative approach with a case study method was used to explore a mother's subjective experience of social support after the death of her child. Data were collected through in-depth interviews with one subject and three informants who were close friends of the subject. The results showed that the subject received social support only from her closest friends and did not receive social support from her family.